Documentación y análisis de las críticas de arte sobre el escultor Julio Antonio «el amado de la crí - Gómez Alfeo, María Victoria; García Rodríguez, Fernando (Documentación de las Ciencias de la Información, 2004)
Critic note-Biography of the sculptor Julio Antonio (Tarragona, 1889-Madrid, 1919) that is based on recopilation of the documented press articles published in his time about his life and work. Selected and comented documents found in El Sol, El liberal, Heraldo de Madrid, El diluvio, El progreso o Prometeo are chosen, among other publications. Likewise, words from other intelectuals of his time are analized.